The Contradictory Effects of Political Connections and Social Relationships on the Role of Government Internal Auditors - Ekayanti, A.Asma Zulistia; ., Arifuddin; Nohong, Mursalim (Journal of Ecohumanism, 2025)
Previous research has revealed that political connections and social relationships between auditors and their clients often lead to a decline in audit quality. In light of the growing interest in understanding the economic implications of political connections, this paper aims to review empirical studies in the accounting and finance domain that investigate the impact of political connections on the ability of internal auditors to detect fraud. This study adopts a qualitative case study approach, utilizing semi-structured interviews within an internal audit organization in Makassar City, where strong political connections are evident. Our findings indicate that while political connections may enable auditors to detect fraud, they often refrain from reporting it to avoid potential losses and safeguard public interests. Additionally, although social relationships with clients are expected to enhance auditors' competence in detecting fraud, these relationships may simultaneously compromise the independence of internal auditors. This research provides valuable insights for policymakers, standard setters, and regulators to better understand the contradictory effects of political connections on audit quality and fraud detection.